How smart tourism embrace blockchains and smart contracts - Zupan Korže, Saša (Mednarodno inovativno poslovanje, 2019)
The purpose of the research is to investigate the implementation of blockchains (BCs) and smart contracts (SCs) in smart tourism. BCs and SCs in the context of tourism are underexplored. Data were collected and analysed from relevant secondary sources in extensive desktop research between January and August 2018. The results highlight some implemented examples of BCs and SCs in tourism and few that are still in probation phase. The findings are interesting for tourism policymakers, professionals, academics and tourism suppliers who are interested in real value added of BCs and SCs in tourism.
Keywords: blockchain; digital ledger technology; digitalna tehnologija; pametne pogodbe; pametni turizem; smart contracts; smart tourism; tehnologija veriženja blokov